Home, Homes and Homeland in “Things” - Shirley Bricout (Études Lawrenciennes)
This article aims to show how the narrative tensions of the short story “Things” complicate the characters’ relation to places and in particular to home and homeland. Such tensions, intensified by the economy of the short story as genre, fashion Lawrence’s ironic commentary of idealism and materialism. While the characters’ interest in Buddhist thought seems to condition their peripathetic lives, their compulsive hoarding of precious furniture and artifacts during their trips to France and Italy challenges the spiritual quest. First a consideration of the significance of the home in Buddhist thought addresses the scope and limits of renunciation and idealism. Multiplicity, signified in the succession of homes the characters dwell in, and the amount of things they amass, is then shown to grow out of a topographical shift from verticality to horizontality, embedded in the narrative. This collapse is emblematic of the characters’ oscillating values, that redefine the quest as events unfold. Finally, the characters’ return to America, their homeland, in the second part of the story, is considered in the light of dialogical tensions created by discrepancies to be found in the status and figurative language of the American couple.